Public Sector Human Resource Practices to Drive Performance - Manning, Nick; Hasnain, Zahid; Pierskalla, Jan Henryk (World Bank, Washington, DC, 2016)
Many Governments wrestle with the issue of designing an appropriate set of human resource practices to motivate public servants to perform. Identifying the right set of practices for the public sector is a source of some controversy, and passions run high particularly in relation to the use of monetary incentives, often referred to as performance-related pay or performance based pay. This GET note reviews recent research on a range of practices Governments utilize to drive employee performance, which rest on the assumptions that public servants are motivated in two ways: (i) ‘intrinsically’ (i.e. internal factors motivated by ‘the right thing to do’), and (ii) ‘extrinsically’ (i.e., external validation from rewards offered by others). Generally, a Human Resource Management (HRM) system designed to motivate employee performance will utilize practices in two broad categories related to: (i) ‘external incentives’ (e.g., financial incentives), and (ii) ‘opportunities to perform’ focusing on ‘intrinsic’ factors (i.e. self-directed work). Within ‘external incentives,’ a financial incentive may either act over the long term (e.g., deferred compensation) or in the short term (e.g., performance-related pay). This note applies this conceptual framework to more clearly understand the range of practices Governments are using to improve staff performance, as well as the pre-conditions for their success. Given the recent attention on performance-related pay, we take a deeper look at the evidence underlying the shorter term performance-related pay, reviewing evidence from both OECD and middle income countries. Annex one provides a brief overview on the theories of motivation for those interested in the theoretical underpinnings of the work, and annex two presents’ experiences of performance pay in practice. This Note draws heavily from performance-related pay in the public sector: A review of theory and evidence (Hasnain and others 2012), a recent review of the literature in fields including political science, public administration, business management, and psychology.